The Influence of Work Discipline, Communication, and Work Conflict on Employees Performance at PT Pratama Makmur Jaya Medan - Shelly Tamara; Deni Faisal Mirza; Willy Evan Wijaya; Desy Kosasih (International Journal of Social Science and Business, 2021)
Conflicts usually arise in an organization as a result of the various problems in terms of communication, personal relationships or because of the problem of the structure of the organization. The conflict of work can also be interpreted as the behavior of the members of the organization that was devoted to the liberal opposition against the other members. Work conflicts that occur within the company due to the existence of a dispute occurs on the employee in connection with the work and most employees can't work together in the organization of the company. This study aims to examine and analyze the influence of work discipline, communication, and conflict to work on the performance of employees of PT Pratama Makmur Jaya Medan. This research was a descriptive quantitative with explanatory method. Analysis data in this study used multiple regression analysis. Sample collection techniques, namely simple random sampling. The research sample is 106 employees. The test results obtained that the Work discipline is partially positive and significant effect on employee performance at PT Pratama Makmur Jaya Medan. Communications in partial positive and significant effect on employee performance at PT Pratama Makmur Jaya Medan. The conflict partially has positive and significant effect on employee performance at PT Pratama Makmur Jaya Medan. The discipline of work, communication and conflict simultaneously positive and significant effect on employee performance at PT Pratama Makmur Jaya Medan.